Fair shared green and recreational spaces guidelines for gender-responsive and inclusive design Tbilisi Municipality - Asian Development Bank (Manila,Philippines Asian Development Bank, 2021)
This publication aims to inform the sustainable development of Tbilisi to give residents a better quality of life while protecting their heritage and preserving the green landscape. The guidelines identify priorities for improvements and for ensuring that limited resources are targeted at the areas of most need. They were developed jointly by the Asian Development Bank and the Municipal Department of Environmental Protection of Tbilisi City Hall.
Introduction - - Urban Green Spaces and Gardens in Tbilisi - - Principles and Steps in Gender-Responsive and Inclusive Design of Green and Recreational Spaces - - Considerations in Gender-Responsive and Inclusive Design of Green and Recreational Spaces - - Standards and Criteria for Detailed Park Design - - Appendixes.
Keywords: Sustainable urban development -- Tbilisi,Georgia; City planning -- Tbilisi,Georgia